Tuning the Catalytic Activity of Ir@Pt Nanoparticles Through Controlling Ir Core Size on Cathode Performance for PEM Fuel Cell Application - Zheng, Hao-Bo; An, Lu; Zheng, Yuying; Qu, Chong; Fang, Yanxiong; Liu, Quanbing; Dang, Dai (Frontiers in Chemistry, 2018)
Pulse electrochemically synthesis of a series of core-shell structured Ir@Pt/C catalysts in cathode catalysts layer are achieved to fabricate membrane electrode assemblies (MEA) with cathode ultra-low Pt loading. The single cell performance of the MEAs in a H2/air PEMFC greatly rely on the sizes of the Ir core nanoparticle, and the optimum activity occurs with Ir core size of 4.1 nm. The cathode MEA with core-shell structured catalysts with optimal Ir core size exhibited excellent performance in a H2/air single fuel cell, comparable to that of a commercial Pt/C MEA (Johnson Matthey 40% Pt), even though the Pt loading in Ir@Pt was only 40% that of the commercial Pt cathode (0.04 vs. 0.1 mg cm–2). The catalysts were characterized by X-ray diffraction, X-ray photoelectron spectroscopy (XPS) and scanning transmission electron microscopy. Based on the characterization results, especially from XPS, we suggest that the effect of Ir core particle size on MEA performance may arise from the interactions between the Pt shell and the Ir core. The XPS results showed that the Ir@Pt/C-300 catalyst has the highest Pt0 fraction among the four tested samples. This work demonstrates the alternative to enhance the cathode performance in single cell of Pt-based core-shell structured catalysts by varying size of the core metal under the Pt shell.